Christianity in Blue : How the Bible, History, Philosophy, and Theology Shape Progressive Identity - Kaden, David A., 1977- (Book collections on Project MUSE., 2021)
Christianity in Blue shows how liberal values and progressive attitudes are the fruits of taking seriously both the Bible and Christian tradition. But rather than treating these sources as the final word, Kaden argues that they are places to start exploring how to be a Christian in the world. Christianity in Blue helps both progressive and conservative Christians better understand the importance of the Bible, theology, history, and philosophy for building a loving church for everyone.